2021
DOI: 10.3390/ijerph18010330
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19—Awareness and Practice of Dentists in Saudi Arabia

Abstract: Dental professionals have a major role in the fight against the spread and transmission of COVID-19. This study aimed to evaluate awareness and practice of dentists in Saudi Arabia regarding COVID-19 and the utilization of infection control methods. A 24-item questionnaire was developed and distributed through social media to 627 dentists working in Saudi Arabia. 177 questionnaires were completed (28.2% response rate). Most dentists were aware about the transmission, incubation time and main clinical symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
2
9
1
Order By: Relevance
“…Several studies with similar outcomes are reported from Saudi Arabia. [29][30][31] All these studies had lower response rate than our study.…”
contrasting
confidence: 69%
“…Several studies with similar outcomes are reported from Saudi Arabia. [29][30][31] All these studies had lower response rate than our study.…”
contrasting
confidence: 69%
“…These findings are consistent with a study conducted among Turkish dental professionals that revealed higher knowledge about the COVID-19 aetiology, mode of transmission and the pre-procedural cautions among dental specialist respondents. These findings indicate a direct correlation between professional experience and LOA which is in total agreement with the previous studies [ 12 , 31 ] and disagreement with other studies reported from in Saudi Arabia [ 28 ] and Jordan [ 28 , 32 ]. The variation in LOA could be attributed to the difference in perception and education of the DHCP.…”
Section: Discussionsupporting
confidence: 52%
“…The response rate of similar studies conducted in Saudi Arabia was 28.7% [ 28 ], 28.2% [ 29 ] and 21.7% [ 30 ]. These values are much lower than our study’s response rate of 60.5%, probably due to variation in the target population.…”
Section: Discussionmentioning
confidence: 99%
“…26 Taken together, increasing the accessibility to materials provided by health care authorities, intensive training programs for all categories of the healthcare workers, rigorous attentive protocols, and a commitment to change behavior/practice, will significantly benefit the spread of the outbreaks. 24,31,32,37,[40][41][42][43][44][45]47,48,60,78,84,131 Mushi et al suggested that "risk communication as an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia". 89 Measures to enhance protection for HCPs and minimize psychological consequences/potential social stigmatization should be recognized in the planning stage before any pandemic.…”
Section: Participants Online Questionnairementioning
confidence: 99%